Mechanisms of receptor tyrosine kinase signaling diversity: a focus in cardiac growth - Vaparanta, Katri (fi=Turun yliopisto|en=University of Turku|, 2023)
To understand organism function and disease and to target perturbed processes for therapy, comprehensive knowledge of the underlying cell signaling networks is required. However, mapping the interplay of the vast number of biomolecules involved in these networks remains challenging. As a result, efforts have focused on identifying the structural elements within biomolecules that facilitate signal transmission. Receptor tyrosine kinases (RTKs) regulate the function of several important organs and are most recognized as oncogenes in cancer. Research into the structural determinants of RTKs that govern their signaling has led to clinically approved therapies. However, some structural regions of these kinases remain poorly understood. In this thesis, the diversity of cell signaling arising from variation in an overlooked region in RTKs known as the extracellular juxtamembrane region was explored. A sequence motif that controls the cell surface location and the signaling of RTKs was identified, presenting a potential novel way to target RTKs for therapy. The cell signaling pathways that regulate myocardial growth could be putatively re-activated to treat heart failure or inhibited to treat pathological hypertrophy. Additionally, these pathways may hold the key to regenerating the myocardium post-injury. A pathway promoting myocardial growth involving STAT5b and the RTK ErbB4 was uncovered in this thesis. VEGFB, traditionally associated with endothelial cells, was additionally observed to elicit myocardial growth through paracrine signaling involving ErbB RTKs. Activation of ErbB4 pathways in the heart with NRG-1 has improved the cardiac function of heart failure patients implying that the discoveries made in this thesis may aid in heart failure therapy development. Finally, recent developments in omics technologies have facilitated the detection and quantification of the different layers of cell signaling networks. Consequently, a growing need for computational analyses capable of reverse-engineering cell signaling pathways from multi-omics data has emerged. In this thesis, a new computational approach specifically designed to discover cell signaling pathways from multi-omics data without the use of prior information was developed. These types of de novo methods remain essential for uncovering new cell signaling connections, which, in turn, can unveil potential new drug targets to treat disease.

Reseptorityrosiinikinaasien viestinnän monimuotoisuuden mekanismit: painotus sydänlihaksen kasvussa Elimistön toiminnan ja sairauksien ymmärtäminen sekä lääkekehitys edellyttää kattavaa tietoa solujen soluviestintäverkostoista. Koska soluviestintämolekyylejä on lukuisia, soluviestinnän tutkimus on keskittynyt löytämään toistuvia rakenteellisia soluviestintää välittäviä alueita soluviestintämolekyyleistä. Reseptorityrosiinikinaasit (RTK:t) ovat solun pinnan soluviestintämolekyylejä, jotka säätelevät useita elimistön tärkeitä toimintoja ja joiden rakenteen tutkimus on johtanut useisiin käytössä oleviin lääkkeisiin. RTK:iden rakenteessa sijaitsee alue solun ulkopuolella, jonka merkitystä ei ole aikaisemmin juurikaan selvitetty. Tämän alueen vaikutusta RTK:iden viestinnän monimuotoisuudelle tutkittiin tässä väitöskirjassa. Alueelta löydettiin sekvenssimotiivi, joka säätelee RTK:iden sijaintia solun pinnalla sekä niiden viestintää. Alueelle voidaan tulevaisuudessa mahdollisesti kohdentaa RTK:iden viestintää muuttavia lääkkeitä. Soluviestintäreittejä, jotka säätelevät sydänlihaksen kasvua, voidaan mahdollisesti aktivoida sydämen vajaatoiminnan hoitamiseksi tai estää vahingollisen sydämen liikakasvun lieventämiseksi. Lisäksi näitä soluviestintäreittejä voidaan hyödyntää vaurion jälkeiseen sydänlihassolujen regeneraatioon. Sydänlihaksen kasvun soluviestintäreitteihin liittyviä havaintoja tehtiin tässä väitöskirjassa. RTK ErbB4:n todettiin aiheuttavan sydänlihaksen kasvua STAT5b viestinnän kautta. RTK ligandi VEGF-B:n puolestaan todettiin vaikuttavan sydänlihaksen kasvuun ErbB RTK:iden viestinnän avulla. Koska ErbB4 viestinnän aktivointi on parantanut sydämen vajaatoimintapotilaiden sydämen toimintaa, nämä havainnot saattavat edesauttaa sydämen vajaatoiminnan hoitojen kehitystä. Omiikka-teknologioilla voidaan mitata soluviestintäverkostojen eri tasoja lähes kattavasti. Laskennallisia työkaluja kuitenkin tarvitaan, jotta omiikka-teknologioilla tuotettu tieto voidaan mallintaa soluviestintäreiteiksi. Uusi soluviestintäreittien mallinnusohjelma kehitettiin tässä väitöskirjassa. Mallinnusohjelma käyttää ainoastaan omiikka-teknologioilla saatua tietoa soluviestintäreittien mallinnukseen. Tämän kaltaisia vain mitattuun tietoon perustuvia menetelmiä tarvitaan uusien soluviestintäreittien löytämiseksi. Uudet soluviestintäreittien yhteydet puolestaan voivat paljastaa uusia tautimekanismeja ja toimia uusina lääkekohteina.